Strategi Komunikasi Pemasaran Hotel AP Premier Dalam Meningkatkan Kepercayaan Khalayak Pada Masyarakat Kota Batam - Gea, Liberniat; Rorong, Michael Jibrael (SCIENTIA JOURNAL, 2024)
In the development of the hotel and tourism business in Indonesia, hotels with various star ratings use different communication strategies. This highlights the importance of strong marketing strategies to achieve the hotel's profit targets. Hotel AP Premier Batam is a 4-star hotel in Batam. This study aims to understand the marketing communication strategy of Hotel AP Premier in increasing public trust through a qualitative approach using Michael Eugene Porter's Competitive Positioning theory. Data collection methods included observation, interviews, and documentation with the research object being the Sales & Marketing department of Hotel AP Premier. The results show that the form, pattern, and marketing communication strategy to increase public trust align with Michael Porter's competitive positioning theory, which considers five competitive forces in the market: competition among similar companies, the entry of new competitors, the development of substitute products, the bargaining power of suppliers, and the bargaining power of consumers. Through this model, the study offers a strong framework for understanding the market position of Hotel AP Premier Batam and how it can achieve a competitive advantage.Keywords: Communication strategy, marketing, forms of communication, communication patterns.